Knowledge on Preconception Care among Reproductive Age Women in Bharatpur Hospital - Paudel, Madhu Maya; Parajuli , Sumitra; Dhakal, Bijaya (Journal of Bharatpur Hospital, 2025)
Background Knowledge on preconception care (PCC) among reproductive-age women is essential to ensure a healthy pregnancy, the health of the future child, and the prevention of reproductive health related complications. The study aim was to find the level of knowledge on preconception care among reproductive age women. MethodsA descriptive cross-sectional study conducted among 230 reproductive aged women attending antenatal outpatient department at Bharatpur Hospital from 15 January to 15 February 2025 for antenatal checkup. Data was collected through semi-structured interview schedule and analyzed using SPSS 16 version. Data was analyzed using descriptive and inferential statistics such as frequency, percentage, mean, standard deviation and Chi-square test. ResultsThe overall findings of the study revealed that majority of the respondents (96.31%) had good level of knowledge and 3.68 % had poor level of knowledge regarding preconception care. The mean score for the level of knowledge was 33.43±5.09. Among the four aspects of PCC, cent percent respondents had good knowledge on reproductive health risk factors and 40% of respondents were intervention aspect of preconception care.. The level of knowledge on preconception care was statistically significant with ethnicity (p